HLA-Cw6 and HLA-DRB1*07 together are associated with less severe joint disease in psoriatic arthritis. Issue 6 (12th January 2007) - Ho, Pauline Y P C; Barton, Anne; Worthington, Jane; Thomson, Wendy; Silman, Alan J; Bruce, Ian N
Abstract : Background: Human leucocyte antigen (HLA) genes predict disease severity in psoriasis ( HLA-Cw6 ) and rheumatoid arthritis (shared epitope (SE)), but the situation is unclear for psoriatic arthritis (PsA). Aim: To determine the association of the HLA-Cw6 and HLA-DRB1 gene with disease severity in a large UK cohort with PsA. Methods: Genotyping of the HLA-Cw and HLA-DRB1 loci was undertaken in DNA samples from patients with PsA (n = 480). Stratification and regression analysis were used within the PsA cases to determine whether HLA-Cw6, HLA-DRB1 or the presence of the SE alleles predicted disease severity as measured by the Health Assessment Questionnaire score, the total number of damaged or involved joints adjusted for disease duration and disease-modifying antirheumatic treatments. Results: HLA-Cw6 was found to be in linkage disequilibrium with HLA-DRB1*07 (r 2 = 0.46). Patients with PsA who carried both HLA-Cw6 and HLA-DRB1*07 had fewer damaged or involved joints (41% fewer damaged (95% CI 23% to 55%, p = 0.02) and 31% fewer involved joints (95% CI 16% to 44%, p<0.001)) compared with those who carried neither HLA-Cw6 nor HLA-DRB1*07 alleles. Those who carried either HLA-Cw6 or HLA-DRB1*07 alleles alone had no evidence of a reduction in joint involvement. The SE, HLA-DRB1 *03 and HLA-DRB1*04 alleles did not predict severity using these outcome measures. Conclusion: Patients with PsA carrying both HLA-Cw6 and HLA-DRB1*07 alleles have a less severe course of arthritis. This suggests that a protective locus lies on a haplotype marked by these alleles. No association was detected with disease severity and SE status.